2004
DOI: 10.1111/j.0963-7214.2004.00501001.x
|View full text |Cite
|
Sign up to set email alerts
|

Beyond Money

Abstract: SUMMARY-Policy decisions at the organizational, corporate, and governmental levels should be more heavily influenced by issues related to well-being--people's evaluations and feelings about their lives. Domestic policy currently focuses heavily on economic outcomes, although economic indicators omit, and even mislead about, much of what society values. We show that economic indicators have many shortcomings, and that measures of well-being point to important conclusions that are not apparent from economic indi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
292
2
21

Year Published

2009
2009
2018
2018

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 1,804 publications
(372 citation statements)
references
References 245 publications
8
292
2
21
Order By: Relevance
“…[14][15][16][17][18][19][20][21] There are studies of socioeconomic differences and health [22,23] as well as cultural differences and health. [24,25] Family income is a key determinant of health child development, reducing the children's likelihood of incurring certain illnesses and cushioning the consequences of ill-health.…”
Section: Introductionmentioning
confidence: 99%
“…[14][15][16][17][18][19][20][21] There are studies of socioeconomic differences and health [22,23] as well as cultural differences and health. [24,25] Family income is a key determinant of health child development, reducing the children's likelihood of incurring certain illnesses and cushioning the consequences of ill-health.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, increases in income and attachment to money have been found to be associated with increases in distrust, depression (Diener and Seligman, 2004), isolation and alienation (Fournier and Richins, 1991;Wuthnow, 1994;Schwartz, 2000;Hammerslough, 2001;Kasser, 2002;Griffin, 2010). In his seminal book The Higher Price of Materialism, Kasser (2002) reported that people with higher levels of economic achievement had weaker relationships with the community and that their materialism was related to low self-esteem and anxiety.…”
Section: Introductionmentioning
confidence: 99%
“…However, they are not constructed to, nor do they, assess the social or economic welfare of countries. For example, Diener and Seligman (2004) point out that decreasing mental health may increase GDP if more money is spent on care. "Paradoxically," they write, "a mounting problem in well-being might increase economic indicators, and the increase in GDP does not indicate whether the money is spent effectively" (p. 17).…”
Section: National Progress Indicators and Well-beingmentioning
confidence: 99%
“…The definition and measures also have an impact on societies as SWB measures are used for evaluating national progress. Diener and Seligman (2004) point out that what is measured by societies is likely to receive more attention and in turn be the very thing to which meaning is attached and ultimately pursued. This raises the question: What exactly should be defined and measured as SWB?…”
Section: Introductionmentioning
confidence: 99%